2002
DOI: 10.17221/4368-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrogen fertilization, sowing rates and site on yields and yield components of selected varieties of safflower (Carthamus tinctorius L.)

Abstract: Field trials were conducted at two sites Troubsko near Brno and Prague-Ruzynì in 19961999 with three varieties of safflower (Gila, Sironaria). Three rates of nitrogen fertilization were used: N 0 = no fertilization, N 1 = 40 kg.ha 1 , N 2 = 80 kg.ha 1 . Sowing rates were 50 and 70 germinable seeds per m 2 . The average values of oil content were highest in seeds of CW-74 variety (27.2%). Gila had on average the lowest oil content (24.5%). Linoleic acid was dominant in all three safflower varieties. Variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The highest number of seeds per head by the nitrogen fertilization increased seed yield per plant, and therefore contributed positively to the seed yield per hectare in the trial. Strasil and Vorlicek (2002); Singh and Singh (2013) and Eryigit et al (2015) reported that the nitrogen fertilization increased yield was consistent with our research results. As the Zn3 application gave the highest number of seeds per head (15.6 pcs head -1 ) in the first year, there were no statistically significant differences between the applications in the second year.…”
Section: Number Of Seeds Per Head (Pieces Head -1 )supporting
confidence: 92%
See 1 more Smart Citation
“…The highest number of seeds per head by the nitrogen fertilization increased seed yield per plant, and therefore contributed positively to the seed yield per hectare in the trial. Strasil and Vorlicek (2002); Singh and Singh (2013) and Eryigit et al (2015) reported that the nitrogen fertilization increased yield was consistent with our research results. As the Zn3 application gave the highest number of seeds per head (15.6 pcs head -1 ) in the first year, there were no statistically significant differences between the applications in the second year.…”
Section: Number Of Seeds Per Head (Pieces Head -1 )supporting
confidence: 92%
“…It was reported by many researches that the nitrogen fertilizer affected on the safflower growth, yield and quality properties significantly (Ahmed et al, 1985;El-Nakhlawy, 1991;Ibrahim, 1994). N fertilization increased seed yield (Strasil and Vorlicek, 2002); 300, 600 and 900 kg ha -1 N applications according to the control plots increased the biomass of safflower by 13.4%, 15.3% and 22.9% respectively (Haghighati, 2010). Nitrogen was effective on the vegetative and reproductive stages of safflower (Bitarafan et al, 2011); nitrogen applications increased seed yield 44.6-60.5% on average compared to the control plots (Singh and Singh, 2013); seed yield, 1000 seed weight, number of heads per plant and plant height were affected positively (Eryigit et al, 2015), and plant height and seed yield were increased ( the nitrogen fertilization.…”
Section: Introduction and Literature Reviewmentioning
confidence: 98%
“…Its seed production in some regions of world, especially some European countries (Overeem et al 1999), faces the alterations in environmental conditions during the growth period due to relatively unsteady wet climates (Van Soest et al 1987;Strasil and Kas 2005). In addition, the influence of planting dates on growth, yield and chemical components was recently reported (Badawy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, over-fertilization and insufficient fertilization lead to economic losses and discharge an excessive amount of nitrogen in the nitrate form through washing [6]. Therefore suggestions for fertilizers with nitrogen should be made so as to ensure a highquality product, optimum yield, high profit and less environmental pollution risks [7].…”
Section: Introductionmentioning
confidence: 99%